Edukasi Kesehatan Maternitas Sebagai Upaya Peningkatan Kesejahteraan Ibu Dan Bayi - Rischa Hamdanesti; Dewi Purnamasari (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Maternity health is a crucial aspect of health development because it directly impacts the well-being of mothers and their babies. Lack of maternal knowledge and skills regarding health care during pregnancy, childbirth, the postpartum period, and newborn care remains a contributing factor to maternity and neonatal complications. This Community Service activity aims to improve mothers' knowledge, attitudes, and skills in maintaining maternity health as an effort to improve the well-being of mothers and babies. The activity's implementation methods included health education, interactive discussions, demonstrations and practical practices of maternal and infant care, and evaluation through pre- and post-tests. The activity targeted pregnant women, postpartum women, and mothers with infants. The results showed an increase in maternal knowledge regarding pregnancy health, safe delivery, postpartum care, and newborn care. Furthermore, there was an increase in positive attitudes, maternal preparedness for childbirth, and infant care skills. Maternity health education has proven effective as a promotive and preventive measure in improving the well-being of mothers and babies, and is expected to contribute to reducing the risk of complications and improving the quality of life of both mothers and babies.